PENGARUH INFLUENCER MARKETING, LIFESTYLE, E WOM TERHADAP MINAT BELI PRODUK FASHION MUSLIMAH (STUDI KASUS PADA MAHASISWI DI SURAKARTA) - Dwi Rahmawati; Ari Susanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Finding out how interested female students in Surakarta are in Muslim fashion products is the main goal of this research. Businesses and fashion designers are vying to create the most cutting-edge styles as the demand for fashion is expected to skyrocket, driving the industry forward. Influencers, lifestyle, and electronic word of mouth are a few of the many factors that can entice customers to make a purchase. Participants were surveyed using Google Forms in this quantitative study. In order to represent an unknown population in this study, 117 participants were randomly selected using the hair formula, which entails multiplying the number of indicators by 5-10. Data analysis includes procedures for evaluating data instruments, checking for classical assumptions, and doing multiple linear regression analysis. Data was analyzed statistically using SPSS Statistics for Windows, version 22. The results of this study show that e-WOM has no impact on consumers' intent to buy, in contrast to lifestyle influences and influencers.